Acoustic Rehabilitation of the Church of Santa Ana in Moratalaz, Madrid - BUENO, Ana Marıa; LEÓN, Angel Luis; GALINDO, Miguel (Archives of Acoustics, 2012)
The church of Santa Ana in Moratalaz, Madrid, Spain (1965–1971), is an emblematic work of thearchitect Miguel Fisac. In his long career include interventions in the religious field, constituting one ofthe most important contributions to Spanish religious architecture of the last century. This church isa singular place of worship and architecturally significant, in which the acoustics played an importantrole in the configuration of the spatiality of the church. This paper studies the acoustic behaviour ofthe church and its relationship with its unique structural, spatial and coating material characteristics.The analysis of the current acoustic conditions, with high reverberation times (up to 6 seconds) andpoor intelligibility on the audience, serve as the basis for making an acoustic rehabilitation proposal thatcontributes to improving the sound conditions of the building for the intended use, without distortingthe spatial, formal and material aspects with which the architect conceived the project.